Respuesta :

Answer:

36

Step-by-step explanation:

Here we a given a rule

It say

[tex]x(y[/tex]÷[tex]3)^2[/tex]

And we are given the values of x and y as

x=4 and y = 9

Let us replace them in the rule we are provided with

[tex]4(9[/tex]÷[tex]3)^2[/tex]

Applying DMAS rule, which says, first Division ollowed by Multiplication addition and then subtraction .

We first divide 9 by 3

9÷3 = 3

Hence

[tex]4(9[/tex]÷[tex]3)^2 = 4(3)^2[/tex]

Now we square first

[tex]3^2 = 3 \times 3 = 9[/tex]

[tex]4(3)^2 = 4 \times 9[/tex]

[tex]4(3)^2 = 36[/tex]

Hence our final answer will be 36

ACCESS MORE